UPAYA UNTUK MENINGKATKAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN MEDIA VIDEO PADA SISWA KELAS VI SDN 004 TERATAK BULUH - Helpiyotwitra Helpiyotwitra (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by low student social studies learning outcomes. This study aims to improve social studies learning outcomes by using video media in class VI SDN 004 Teratak Buluh. This research is a classroom action research that includes activities with stages of planning, action, observation and reflection. The results showed that the increase in social studies learning outcomes of class VI students, the average classical completeness before class action research was 75% in the first cycle of 82.14% and in the second cycle it was 92.85%. Scientific performance learning outcomes before class action research is 65.36%, and scientific performance learning outcomes after class action research cycle I is 72.76% increased by 7.4%, and scientific performance learning outcomes after class II cycle action research is 73.17% also increased by 0.41% from cycle I. The occurrence of increased learning outcomes of scientific performance also affects student learning outcomes. Based on the results of classroom action research, it can be concluded that using video media can improve social studies learning outcomes. Grade VI students of SDN 004 Teratak Buluh.